2023
DOI: 10.3390/su15118456
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Big Data Analytics and Knowledge Management on Green Innovation Practices and Organizational Performance: The Moderating Effect of Government Support

Abstract: Understanding and predicting the relationship between big data analytics (BDA) and knowledge management (KM) and how they complement each other is still an ambiguous and strategically crucial issue. This study aims to investigate the interrelationships between BDA and KM in fostering green innovation practices (GIP) and organizational performance and, in addition, to explore the mediation effect of KM and how it can boost the impact of BDA on GIP. Based upon the underpinning theories that cover the study’s res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 90 publications
1
5
0
Order By: Relevance
“…Furthermore, our findings align with previous research and indicate that when a company combines its internal and external resources with all supply chain associates and investors, it is more likely to have enhanced opportunities for innovation [ 12 , 85 ]. Moreover, our research indicates that the implementation of environmentally-friendly managerial innovations is directly correlated with CFP.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, our findings align with previous research and indicate that when a company combines its internal and external resources with all supply chain associates and investors, it is more likely to have enhanced opportunities for innovation [ 12 , 85 ]. Moreover, our research indicates that the implementation of environmentally-friendly managerial innovations is directly correlated with CFP.…”
Section: Resultssupporting
confidence: 90%
“…More energy is conserved, and garbage is diverted from landfills because of these innovations [ 11 ]. For these reasons, businesses frequently adopt G_PROC to boost productivity, save money, and create new opportunities in the market [ 12 ]. Businesses, sectors, and academics all agree that G_PROC is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the study found that GEO partially mediates the BDA-green innovation relationship, revealing that 30.61% of the BDAC effect on GI was explained via the existence of the mediation effect of GEO , inferring that H2a is accepted. Based on the DC theory, GEO benefits from BDA that offers strong support to enhance green innovation by developing new green products and green business models; and reconfiguring green processes to reduce energy consumption and improve ecosystem (Makhloufi et al. , 2023b; Persaud and Zare, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The survey comprised of a series of 21 questions, where participants assessed each question using a five-point Likert scale that ranged from "1: strongly disagree" to "5: strongly agree". The selection of the questionnaire was based on the existing literature, specifically the studies conducted by (Makhloufi et al, 2023;Ramadan et al, 2020). The present study employed partial least squares-structural equation modelling (PLS-SEM) as a statistical software tool for data analysis and hypothesis testing.…”
Section: Methodsmentioning
confidence: 99%
“…In the present day, contemporary firms have recognized and assigned significance to the strategic economic and environmental benefits associated with the digital economy (Bi et al, 2023). The field of big data analytics (BDA) is widely recognized as an essential aspect in the current era, which is marked by notable technological progress (Makhloufi et al, 2023). In the context of Economic Digital Transformation (EDT), emerging firms are actively engaged in the process of digitizing their operations and using substantial data to facilitate informed decision-making.…”
Section: Introductionmentioning
confidence: 99%